Academic Senate Minutes 2011-10-27 - Academic Senate:::::::::
New Major in Early Childhood Studies and Revision to Bi-Disciplinary concentration in Mathematics & Statistics approved by consent. From SDS: Regarding the Subsidization of the new CAPS Student Fee for Pell Grant Students -Second Reading – referred back to committee. Revision to the Grade Appeal, Student Grievance and Cheating and Plagiarism policies – Second Reading – Approved.